Two novel direct SPIO labels and in vivo MRI detection of labeled cells after acute myocardial infarct. (August 2017) - Korpi, Riikka M; Alestalo, Kirsi; Ruuska, Timo; Lammentausta, Eveliina; Borra, Ronald; Yannopoulos, Fredrik; Lehtonen, Siri; Korpi, Jarkko T; Lappi-Blanco, Elisa; Anttila, Vesa; Lehenkari, Petri; Juvonen, Tatu; et al.
Background: Acute myocardial infarction (AMI) is a leading cause of morbidity and mortality worldwide. Cellular decay due hypoxia requires rapid and validated methods for possible therapeutic cell transplantation. Purpose: To develop direct and rapid superparamagnetic iron oxide (SPIO) cell label for a large-animal model and to assess in vivo cell targeting by magnetic resonance imaging (MRI) in an experimental AMI model. Material and Methods: Bone marrow mononuclear cells (BMMNCs) were labeled with SPIO particles using two novel direct labeling methods (rotating incubation method and electroporation). Labeling, iron incorporation in cells and label distribution, cellular viability, and proliferation were validated in vitro. An AMI porcine model was used to evaluate the direct labeling method (rotating incubation method) by examining targeting of labeled BMMNCs using MRI and histology. Results: Labeling (1 h) did not alter either cellular differentiation potential or viability of cells in vitro. Cellular relaxation values at 9.4 T correlated with label concentration and MRI at 1.5 T showing 89 ± 4% signal reduction compared with non-labeled cells in vitro. In vivo, a high spatial correlation between MRI and histology was observed. The extent of macroscopic pathological myocardial changes (hemorrhage) correlated with altered function detected on MRI. Conclusion: We demonstrated two novel direct SPIO labeling methods and demonstrated the feasibility of clinical MRI for monitoring targeting of the labeled cells in animal models of AMI.